2007
DOI: 10.1007/s00216-007-1652-x
|View full text |Cite
|
Sign up to set email alerts
|

Activities and identification of aryl hydrocarbon receptor agonists in sediments from the Danube river

Abstract: This study is a consequence of a distinct fish decline in the Danube river since the beginning of the 1990s. In contrast to the decline of fish population, former studies have repeatedly documented that the water quality along the Danube river is improving. However, the conclusion of a pilot study in 2002 was that a high hazard potential is associated with local sediments. The present study documents that sediment samples from the Danube river showed comparatively high aryl hydrocarbon receptor mediated activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 54 publications
7
78
0
3
Order By: Relevance
“…Hugla et al (1995) correlated alterations in liver ultrastructure similar to our observations to high PCB concentrations in barbel from the River Meuse, and PCBs have also been shown to generate a multitude of hepatic alterations in other studies (Weibel & Paumgartner 1978, Hugla et al 1996, Hugla & Thomé 1999. Indeed, Keiter et al (2008) documented considerably higher concentrations of PCBs in sediments from Sites Rottenacker and Ehingen than in those from Site Riedlingen. Although overall PCB concentrations were comparatively low, PCBs may have accumulated much more strongly in barbel via either food or direct contact with contaminated sediments.…”
Section: Reasons For Fish Decline In the Danube Riversupporting
confidence: 89%
“…Hugla et al (1995) correlated alterations in liver ultrastructure similar to our observations to high PCB concentrations in barbel from the River Meuse, and PCBs have also been shown to generate a multitude of hepatic alterations in other studies (Weibel & Paumgartner 1978, Hugla et al 1996, Hugla & Thomé 1999. Indeed, Keiter et al (2008) documented considerably higher concentrations of PCBs in sediments from Sites Rottenacker and Ehingen than in those from Site Riedlingen. Although overall PCB concentrations were comparatively low, PCBs may have accumulated much more strongly in barbel via either food or direct contact with contaminated sediments.…”
Section: Reasons For Fish Decline In the Danube Riversupporting
confidence: 89%
“…Subsequently, in a mass-balance analysis, it will be assessed whether the chemically determined potency of a fraction can explain the biological responses observed in the bioassay (Keiter et al 2008;Khim et al 1999a, b). Mass-balance estimates of all major compounds contributing to the observed effects can be calculated to elucidate if all of the activity has been identified, and to assess the potential for interactions such as synergism or antagonism among contaminants present in the complex mixtures (Hilscherova et al 2000;Korner et al 2000).…”
Section: The Eda Processmentioning
confidence: 99%
“…With respect to comprehensive toxicological assessments of freshwater systems, the EDA approach was used in several case studies investigating whole catchment areas, providing evidence on the main stressors and possible mitigation measures in order to improve the ecological status of river ecosystems (Brack et al 2005a(Brack et al , 2008aHollert et al 2009a;Keiter et al 2006Keiter et al , 2008Keiter et al , 2009aWeiss et al 2009). However, to date EDA is almost exclusively based on measurable effects in in vitro and in vivo biotests.…”
Section: Use Of Eda In Environmental Risk Assessmentmentioning
confidence: 99%
“…However, TEQ calculated based on these three classes of chemicals often account for less than 20% of the TEQ bio (Kannan et al, 2008;Keiter et al, 2008;Nieuwoudt et al, 2009;Hong et al, 2012;Wang et al, 2014a), which suggests that unknown AhR agonists generally exist in sediments and soils. Similar phenomenon also occurred in other environmental matrix, for example, Muusse et al (2012) found PAH can only explain up to 9% of the AhR agonist activity in roadside snow samples in Norway.…”
Section: Discussionmentioning
confidence: 99%